Antimicrobial secondary metabolites from a marine-derived fungus Penicillium sp. OM07 - Phi, Thi Dao; Nguyen, Thuy Linh; Vu, Van Nam; Vu, Thi Quyen; Nguyen, Mai Anh; Vu, Thi Thu Huyen; Le, Thi Hong Minh; Pham, Van Cuong; Doan, Thi Mai Huong (Vietnam Journal of Marine Science and Technology, 2024)
Eight compounds, diketopiperazine dimer WIN 64821 (1), ergosterol peroxide (2), ergosterol (3), 3β,5α,9α-trihydroxyergosta-7,22-dien-6-one (4), 3,4-dihydroxy-6,7-dimethyl-quinolin-2-carboxylic (5), norhaman (6), dihydrocitrinin (7), and phenol A acid (8) were isolated and characterized from the culture broth of the marine-derived Penicillium sp. OM07 strain was isolated from sediment collecting at Son Cha, Hue, Vietnam. Their structures were determined by analyses of MS and NMR data. All compounds were evaluated for their antimicrobial activity against a panel of clinically significant microorganisms. Most showed high antifungal activity against Candida albicans ATCC10231 strain with MIC values ranging from 8 µg/mL to 256 µg/mL. All compounds had inhibitory activity against from one to three Gram-positive tested strains with MIC values from 64–256 µg/mL.